Integrating comprehensive surgical, intensive, and emergency care systems into the Pan American Health Organization’s health agenda - Maria Jose Garcia Fuentes; Ayla Gerk; Leticia Campos; Alejandro Torres; Taylor Wurdeman; Nikathan Kumar; Ruth Jimbo-Sotomayor; Juan Carlos Salamea; Luiz Fernando dos Reis Falcão; Guido Parquet; John G. Meara; Tarsicio Uribe-Leitz; et al. (Revista Panamericana de Salud Pública)
In October 2024, the Pan American Health Organization (PAHO) formally integrated surgical, intensive, and emergency care into its health agenda. This followed important events, including the June 2024 endorsement of the Strategy on Integrated Emergency, Critical and Operative Care 2025–2030 by the PAHO Executive Committee. This strategy builds on the 2015 World Health Assembly (WHA) Resolution 68.15, which recognized surgery as essential to universal health coverage, and the 2023 WHA Resolution 76.2, which called for standardized emergency preparedness and response. With 365 million Latin Americans lacking access to essential surgical services, the need for a regional action plan is urgent. Ecuador, the first country in Latin America to develop a national surgical, obstetric, and anesthesia plan (NSOAP), highlighted the need for integrated surgical care to address health disparities in the region. While PAHO’s formal integration is commendable, its success will rely on sustained political engagement, financial commitment, and robust monitoring. This article outlines the foundations for this strategy, the mechanisms required for successful implementation, and the role of PAHO and its Member States in strengthening surgical systems as a public health priority. By focusing on vulnerable groups and leveraging collaboration, this initiative can reduce health inequities across the Americas, reinforcing universal health coverage and access to safe, timely, and affordable surgical care.